ECONOMIC OUTPUT, MONETARY POLICY TRANSMISSION AND THE ROLE OF ISLAMIC BANKS: EVIDENCE FROM PAKISTAN DUAL BANKING SYSTEM - Azam Ali; Muhamed Zulkhibri; Tanveer Kishwar (Journal of Islamic Monetary Economics and Finance, 2022)
Using co-integration analysis, this study evaluates the role of Islamic banks in monetary transmission and the economic growth of Pakistani economy. More specifically, it investigates the role of Islamic bank deposits and financing in the transmission of monetary policy impacts to the real economy. The findings suggest that Islamic bank financing and deposits play key roles in Pakistan's monetary transmission process. The bank lending channel has the potential to become a major channel of monetary transmission in Pakistan's economy. The bank lending channel highlights the significance of Islamic financial institutions in disseminating the effects of monetary policy across the economy. Therefore, more efforts should be made to establish a more effective Islamic money market, which might offer Islamic banks with an alternative funding source.